Kajian Adverse Drug Reactions Terkait Interaksi Obat pada Pasien Geriatrik di Salah Satu Rumah Sakit di Jayapura Periode Januari – April Tahun 2023 - Risna; Nago Pita Sari, Nawang Wulan (Media Farmasi, 2024)
Study of adverse drug reactions related to drug interaction in geriatric patients at one of the hospitals in Jayapura from January to April 2023 Cases of therapeutic failure caused by drug interactions in the world are still quite high and one of the patients most vulnerable to drug interactions is geriatric patients due to the use of drug combinations. This study aims to identify the incidence of Adverse Drug Reactions (ADRs) related to drug interactions in inpatient geriatric patients at one of the hospitals in Jayapura. This research is descriptive-analytic in nature using a cross-sectional research design with a retrospective data collection technique using medical record data and prescription review for inpatient geriatric patients in January-April 2023. The sample in this study was 110 inpatient geriatric patients who met the specified criteria. The research results show that the incidence of ADRs related to drug interactions in inpatient geriatric patients in the January-April 2023 period was found to be 81 cases of drug interactions with a severity level of moderate 78% (63 cases), minor 13% (11 cases) and major 9% (7 case). Meanwhile, based on the results of the analysis of drug interaction mechanisms, it was found that pharmacodynamic interactions were 77% (62 cases) and pharmacokinetic interactions were 23% (19 cases). The potential for drug interactions in geriatric patients is still categorized as high. The high potential for drug interactions can have an impact on the pharmacological effects and side effects of the drug. Kasus kegagalan terapi yang diakibatkan oleh interaksi obat di dunia masih cukup tinggi dan salah satu pasien yang paling rentan terhadap interaksi obat adalah pasien geriatrik akibat penggunaan kombinasi obat. Penelitian ini bertujuan untuk mengidentifikasi kejadian Adverse Drug Reaction (ADRs) terkait interaksi obat pada pasien geriatrik rawat inap di salah satu rumah sakit di Jayapura . Penelitian ini bersifat deskriptif analitik menggunakan desain penelitian cross sectional dengan teknik pengambilan data secara retrospektif menggunakan data rekam medik dan kajian resep pada pasien geriatrik rawat inap bulan Januari-April 2023. Sampel dalam penelitian ini sebanyak 110 pasien geriatrik rawat inap yang memenuhi kriteria yang ditetapkan. Hasil Penelitian menunjukkan bahwa kejadian ADRs terkait interaksi obat pada pasien geriatric  rawat inap periode Januari-April Tahun 2023 ditemukan sebanyak 81 Kasus Interaksi Obat dengan tingkat keparahan Moderate 78% (63 kasus), minor 13% (11 kasus) dan major 9% (7 kasus). Sedangkan berdasarkan hasil analisis mekanime interaksi obat diperoleh interaksi farmakodinamik sebesar 77% (62 kasus) dan farmakokinetik sebesar 23% (19 kasus). Potensi kejadian interaksi obat pada pasien geriatrik  masih dikategorikan tinggi. Tingginya potensi kejadian interaksi obat tersebut dapat berdampak pada efek farmakologi dan efek samping dari obat.